Kajian Literatur Tentang Penerapan Aplikasi Wordwall Terhadap Hasil Belajar pada Materi Mengubah Bentuk Energi di Kelas IV SD - Zn, Risma Ayu Oktavia; M, Hanny Nur Jan’nah; Setiyawan, Hery (Indo-MathEdu Intellectuals Journal, 2025)
The problem of low motivation and learning outcomes among elementary school students remains a challenge in the education sector in Indonesia. One alternative solution is the utilization of interactive technology-based learning media, such as the Wordwall application. This study aims to examine the effectiveness of using Wordwall in improving student learning outcomes on the topic of "Transforming Forms of Energy" in fourth-grade elementary school. The method used is a literature review of four articles relevant to the research variables. Based on the review results, Wordwall is an educational application that provides quiz features and interactive games that can increase student engagement actively in the learning process. The use of Wordwall has proven effective in improving students' learning outcomes, in line with the interactive learning theories that underpin this study. However, challenges such as limited internet access and the need for teacher creativity in designing materials remain a concern. Therefore, training for teachers and infrastructure support are needed so that the implementation of this media can run optimally